ENCHANCING AND MONITORING INVESTMENT MECHANISM WHILE PLACING TEMPORARY FREE RESOURCES BY THE FUND OF SOCIAL INSURANCE IN THE RUSSIAN FEDERATION - Andrey A. Elsin (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article provides findings of the research dealing with investment by the Fund of Social Insurance in permitted by legislation assets, analyzes placing of resources by the Pension Fund of Russia, the Funds of Social Insurance of the Russian Federation and the Fund of Obligatory Medical Insurance. The author proposes methodological approaches for raising efficiency of resource placing, including those on legislative level. Findings of this research can be used to enhance profitability of money invested in finance instruments.